Emerging diseases, re‐emerging histories. (27th July 2020) - Green, Monica H.
Abstract: The notion of "emerging infectious diseases" (EID) as a category of global health concerns was created in the 1990s to acknowledge that, although public health interventions, vaccines, and antibiotics since the late 19th century had given wealthier parts of the world control over most infectious diseases, the experience of Ebola and HIV/AIDS showed that new human diseases could still arise. "Emerging diseases" have clear histories, and the task the field of EID set itself has been to make those histories as short as possible—to catch emerging diseases as close to their origin as possible and snuff them out before they can become pandemics. In contrast, many of the known infectious diseases, those that were allegedly "conquered" by the rise of biomedicine in the late 19th and early 20th centuries and which (aside from smallpox) nonetheless still persist today, were assumed to have existed "since time immemorial." Their histories had no specific time‐depth, no documentable origins, and few discernible narrative arcs. The advent of a new field of research, palaeogenetics, has made possible an evolutionary perspective on pathogenic microorganisms, bringing hitherto unimaginable specificity to their documentable histories. Many origin stories, and nearly all globalization stories, fall within periods that historians and archaeologists study intensively. I argue that the diseases that have proved best suited to global expansion since the advent of the Holocene—those that became pandemics, like COVID‐19—are those that have best exploited humans' global networks and behaviors in a given age. This recognition, in turn, gives the fields of both global health and history of medicine a new agenda.